2018
DOI: 10.1159/000487677
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of the Fractional Excretion of Uric Acid with Brachial-Ankle Pulse Wave Velocity and Ankle Brachial Index in Chinese Young Adults

Abstract: Background/Aims: Elevated serum uric acid (UA) was intimately correlated with vascular stiffness and abnormal ankle brachial index (ABI) in various populations. These correlations lost significance after adjustment for estimated glomerular filtration rate (eGFR), indicating that the association of UA and brachial-ankle pulse wave velocity (baPWV) or ABI might be driven by kidney function. UA is predominantly eliminated through the kidneys, and metabolic disorders can influence the clearance of UA. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…The assessment of baPWV was analyzed by a volumeplethysmographic apparatus (BP-203RPEII; Nihon Colin, Tokyo, Japan). Detailed collection information has been reported previously [25,26]. Individuals were asked to maintain a supine position without a pillow.…”
Section: Measurement Of the Bapwv And The Definition Of Arterial Stifmentioning
confidence: 99%
“…The assessment of baPWV was analyzed by a volumeplethysmographic apparatus (BP-203RPEII; Nihon Colin, Tokyo, Japan). Detailed collection information has been reported previously [25,26]. Individuals were asked to maintain a supine position without a pillow.…”
Section: Measurement Of the Bapwv And The Definition Of Arterial Stifmentioning
confidence: 99%
“…BaPWV ≥ 1400 cm/s is an independent variable for risk stratification by Framingham score and for discrimination of subjects with cardiovascular disease. Therefore, high baPWV was defined as baPWV ≥ 1,400 cm/s [ 30 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Markers of Arterial Stiffness. BaPWV was measured using a volume-plethysmographic device (BP-203RPEII, Nihon Colin, Japan) as previously reported [25,30,[35][36][37]. The average value of baPWV values on both sides was used for analysis.…”
Section: Laboratorymentioning
confidence: 99%
See 1 more Smart Citation
“…Brachial–ankle pulse wave velocity (baPWV) measurement is a validated method for quantifying arterial stiffness [9]. baPWV is easy and convenient to perform and can be widely used in large-scale populations and clinical settings [911]. Prior studies have suggested that the principal determinants of PWV progression are a number of cardiovascular risk factors, such as dyslipidemia, obesity, diabetes, elevated blood pressure (BP), higher heart rate (HR) and chronic kidney disease [1216].…”
Section: Introductionmentioning
confidence: 99%